Geometric methods in the planning of urban transport networks - Kuspekov , Кайырбек (Рroblems of engineering and professional education, 2023)
The article deals with the actual problems of planning the transport networks of the city, which is based on roads. This problem covers the formulation and solution of various engineering problems. Optimization geometric planning models are proposed based on the construction of the shortest orthogonal lines and rectangles on a plane, which increase the efficiency of designing and choosing the best plan option.